2018
DOI: 10.12991/mpj.2018.69
|View full text |Cite
|
Sign up to set email alerts
|

Feedback for a simulation practice on communication skills in pharmacy education: A pilot study

Abstract: Although simulation practice with standard patients became popular in curriculums since years of various countries, it hasn't been used in the education of pharmacists and pharmacy technicians in Turkey yet. In this study, it is aimed to conduct a pilot study with standard patients on students in the simulation laboratory for the first time and get feedback of them. This study was conducted with 22 pharmacy technicians, four pharmacy students and four standard patients in 15-16 December 2015. Six scenarios wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…It is indicated that scenarios reflecting real situations (environment, atmosphere, interpersonal difficulties, etc.) contribute to the development of communication skills of future medical workers (Bressmann & Eriks-Brophy, 2012;Putter-Katz et al, 2018;MacLean, Geddes, Kelly, & Della, 2018;Ulutaş, Sözen, Yeğenoğlu, & Elçin (2018). It is noted by Kaplonyi et al (2017) that programs based on the "standardized patient" methodology are widely recognized as an effective means of teaching communication skills, but there is insufficient evidence of how this affects patient outcomes and the economic benefits of this training method are not indicated.…”
mentioning
confidence: 99%
“…It is indicated that scenarios reflecting real situations (environment, atmosphere, interpersonal difficulties, etc.) contribute to the development of communication skills of future medical workers (Bressmann & Eriks-Brophy, 2012;Putter-Katz et al, 2018;MacLean, Geddes, Kelly, & Della, 2018;Ulutaş, Sözen, Yeğenoğlu, & Elçin (2018). It is noted by Kaplonyi et al (2017) that programs based on the "standardized patient" methodology are widely recognized as an effective means of teaching communication skills, but there is insufficient evidence of how this affects patient outcomes and the economic benefits of this training method are not indicated.…”
mentioning
confidence: 99%